Can Strain Imaging Predict Left Ventricle Remodeling? A Study from Eastern India - Rakesh Agarwal; Soumya Kanti Dutta; Rashmi Baid; Dhurjati Prasad Sinha (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging, 2021)
Background: Even persistently patent infarct-related artery has been shown to be associated with left ventricle (LV) remodeling. The purpose of this study was to evaluate the role of LV strain imaging by echocardiography in predicting LV remodeling in patients undergoing coronary revascularization. Materials and Methods: A total of 104 patients between the ages of 18 and 75 years of age undergoing percutaneous transluminal coronary angioplasty (PTCA) for acute coronary syndrome (ACS) were selected and subsequently followed up for 3 months. Echocardiography was obtained before PTCA and subsequently 3 months later with global longitudinal strain (GLS) measurements. Results: In our study, 24% patients studied developed LV remodeling at 1 month even after clinical, angiographic, and procedural success of percutaneous intervention. A value of LV GLS <−10.8 predicted the development of LV remodeling with 80% sensitivity and 86% specificity with lower values having higher specificity. Conclusions: GLS assessment by echocardiography in the acute setting is feasible and easy to do with no complications and may be used with considerable sensitivity in predicting patients with adverse remodeling after ACSs.